Liquid silicone rubber composite material and preparation method thereof

CN122978726APending Publication Date: 2026-10-27DONGGUAN PROSOFTT ELECTRONIC TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611370317.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]现有液态硅胶和硅橡胶体系中,常通过气相二氧化硅等增强填料改善强度和抗撕裂性能,但增强相表面活性较高,分散不充分时容易形成团聚并提高体系黏度,使加工流动性和表面均匀性受到影响;也有方案通过引入游离硅油或润滑性组分降低摩擦,但游离组分可能在固化、抽提或长期使用中迁移,进而削弱力学强度和持久低摩擦表现

Benefits of technology

1.通过将羟基封端聚二甲基硅氧烷固定于气相二氧化硅—硅酸三甲基甲硅基酯形成的表面和界面,增强填料的分散状态与润滑单元的位置得到协同调节,相比游离润滑相直接加入方式,有利于降低迁移风险并保持较稳定的低摩擦表现。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978726A_ABST
    Figure CN122978726A_ABST
Patent Text Reader

Abstract

The application belongs to the field of high polymer composite materials and provides a liquid silicone rubber composite material and a preparation method thereof. The application matches the proportion of hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch, hydrogen-containing siloxane copolymer, platinum complex and inhibitor to form a two-component addition type liquid silicone rubber system, realizes the compromise of the silicone rubber product in mechanical strength, low friction retention, residual volatile control and batch stability after curing, solves the problem that the reinforced phase and the free lubricating phase are mutually restrained and the processing fluidity and the low migration performance are difficult to unify, and is suitable for sealing, friction reduction and elastic product scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer composite materials, and more specifically to a liquid silicone composite material and its preparation method. Background Technology

[0002] Liquid silicone materials are widely used in seals, friction-reducing gaskets, elastic contacts, flexible coverings, medical and everyday elastic products due to their injection molding, compression molding, casting, low curing shrinkage, good weather resistance, and strong elastic recovery. These applications typically require materials to remain flowable, degassable, and moldable within a wide processing window, while maintaining stable mechanical load-bearing capacity, tear resistance, compression recovery, low surface friction, and low migration properties after curing. For dynamic seals, sliding contacts, and flexible assembly parts, the material must avoid deformation, tearing, and compression failure due to insufficient reinforcement, while also avoiding assembly obstruction, increased wear, and increased noise due to excessive surface friction. Therefore, achieving a balance between reinforcement, lubrication, low migration, and processing adaptability is a crucial direction for the development of highly reliable elastic products from liquid silicone composite materials.

[0003] In existing liquid silicone and silicone rubber systems, strength and tear resistance are often improved by reinforcing fillers such as fumed silica. However, the reinforcing phase has high surface activity, and insufficient dispersion can easily lead to agglomeration and increase the viscosity of the system, affecting processing flowability and surface uniformity. Other approaches reduce friction by introducing free silicone oil or lubricating components, but these free components may migrate during curing, extraction, or long-term use, thus weakening mechanical strength and sustained low-friction performance. For example, Chinese patent CN107815124A discloses a self-lubricating silicone rubber and its preparation method, which uses methyl vinyl silicone rubber, fumed silica, hydroxyl silicone oil, fluorinated release agent, methyl phenyl silicone oil, and magnesium oxide to reduce surface friction. However, this approach, which relies on a combination of free lubricating components and conventional fillers, may still suffer from problems such as lubricating phase migration, insufficient dispersion stability of the reinforcing phase, and difficulty in simultaneously stabilizing low-friction durability and mechanical properties. Summary of the Invention

[0004] The purpose of this invention is to provide a liquid silicone composite material and its preparation method, which solves the problem that it is difficult to simultaneously achieve mechanical strength and durable low friction performance, as well as processing fluidity and low migration performance in current liquid silicone systems.

[0005] This invention fixes hydroxyl-terminated polydimethylsiloxane onto the surface and interface formed by fumed silica-trimethylsiloxane and matches it in proportion with vinyl-terminated polydimethylsiloxane and hydrogen-containing siloxane copolymer. This weakens the interfacial constraint caused by the reinforcing filler and the migration softening caused by the free lubricating phase, thereby achieving a balance of mechanical strength, durable low friction, processing fluidity and low migration performance.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A liquid silicone composite material, comprising 100 parts by weight of vinyl-terminated polydimethylsiloxane added in the final mixing stage, includes the following feed components: Vinyl-terminated polydimethylsiloxane, 100 parts by weight; Hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch, 15-45 parts by weight, wherein the hydroxyl-terminated polydimethylsiloxane in the masterbatch has a fixation rate of 70-95 wt% relative to its feed amount; Trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer, 1.0-8.0 parts by weight; The zero-valent platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex solution contains 5-40 mg / kg of platinum element in the total mass of the feed components. 1-Ethynylcyclohexanol, 0.01-0.20 parts by mass, and the molar ratio of silicon-hydrogen bonds to vinyl groups in the liquid silicone composite material is 0.80:1-1.60:1.

[0007] Furthermore, the hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricant masterbatch comprises fumed silica, trimethylsilyl silicate, and hydroxyl-terminated polydimethylsiloxane. The hydroxyl-terminated polydimethylsiloxane exists, at least in part, in an immobilized state that is retained after toluene extraction on the surface and interface formed by the fumed silica and the trimethylsilyl silicate. The liquid silicone composite material is cured to form a silicone rubber product.

[0008] Furthermore, the hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsiloxane composite reinforced lubricant masterbatch is prepared through the following steps: A1. Provides a predispersant of fumed silica-trimethylsilyl silicate; A2. Based on 100 parts by weight of the fumed silica, add 5-30 parts by weight of hydroxyl-terminated polydimethylsiloxane; A3. The fumed silica-trimethylsilyl silicate predispersant is mixed with the hydroxyl-terminated polydimethylsiloxane to obtain a mixture; A4. The mixture is heat-treated to fix the hydroxyl-terminated polydimethylsiloxane on the surface and interface of the fumed silica-trimethylsilyl silicate pre-dispersion, thereby obtaining the hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch.

[0009] Furthermore, in step A3, the mixing is carried out under an industrial nitrogen atmosphere at 60-100°C for 0.5-2.0 hours; In step A4, the heat treatment is carried out at 110-150℃ and an absolute pressure of 0.002-0.020MPa for 1-4 hours; After the heat treatment is stopped, the mixture is cooled to 20-40°C under an industrial nitrogen atmosphere to obtain the hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch. The fixation rate was determined by the toluene extraction mass difference method.

[0010] Furthermore, the fumed silica-trimethylsilyl silicate predispersant is prepared by the following steps: B1. Add 100 parts by weight of fumed silica, 20-80 parts by weight of trimethylsilyl silicate and 30-120 parts by weight of vinyl-terminated polydimethylsiloxane to a mixing device; B2. The fumed silica, the trimethylsilyl silicate, and the vinyl-terminated polydimethylsiloxane are mixed and degassed, wherein the mixing is carried out at 40-90°C for 0.5-3.0 h, and the degassed is carried out at 60-100°C and an absolute pressure of 0.002-0.030 MPa for 0.5-2.0 h, to obtain the fumed silica-trimethylsilyl silicate predispersant.

[0011] Furthermore, in the hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricant masterbatch, the mass ratio of fumed silica to trimethylsilyl silicate is 100:20-100:80, and the mass ratio of hydroxyl-terminated polydimethylsiloxane to fumed silica is 5:100-30:100; The vinyl-terminated polydimethylsiloxane has a viscosity of 500-100000 mPa·s and a vinyl content of 0.05-1.20 wt%. The trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer has a hydrogen content of 0.10-1.60 wt%, and the molar ratio of silicon-hydrogen bonds to vinyl groups in the liquid silicone composite material is 0.80:1-1.60:1.

[0012] Furthermore, the liquid silicone composite material is a two-component addition-type liquid silicone system; The two-component addition-type liquid silicone system includes component A and component B; Component A contains the vinyl-terminated polydimethylsiloxane, the hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch, and the zero-valent platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex solution. Component B contains the vinyl-terminated polydimethylsiloxane, the hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch, the trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer, and the 1-ethynylcyclohexanol.

[0013] Furthermore, the coefficient of dynamic friction of the liquid silicone composite material after curing, as measured according to American Society for Testing and Materials (ASTM) standard D1894, is 0.20-0.65. The cured liquid silicone composite material has a Shore A hardness of 20-80, a tensile strength of 5-12 MPa, a tear strength of 15-45 kN / m, and a compression set of 8-25%.

[0014] This invention also discloses a method for preparing the aforementioned liquid silicone composite material, comprising the following steps: S1. Provide a pre-prepared hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch; S2. Based on 100 parts by weight of the vinyl-terminated polydimethylsiloxane, add 15-45 parts by weight of the hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch, mix, and obtain the base adhesive. S3. The base adhesive is divided into component A and component B. The zero-valent platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex solution is added to component A. The trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer and 1-ethynylcyclohexanol are added to component B. S4. Mix the components A and B and then cure them to obtain a cured silicone rubber product.

[0015] Furthermore, in step S2, the mixing is carried out at 25-80°C for 0.5-3.0 hours, and the mixing is performed using one or more of a vacuum kneading device, a planetary mixing device, or a three-roll mill. After mixing, the aggregate D90 of the hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsiloxane composite reinforced lubricant masterbatch in the base adhesive is 5-80 μm. The base adhesive is degassed for 0.5-2.0 hours under reduced pressure conditions of 0.002-0.030 MPa.

[0016] Furthermore, in step S3, the mass ratio of component A to component B is 1:0.8 to 1:1.2.

[0017] Furthermore, in step S4, the curing is one of injection molding curing, compression molding curing, or casting curing, and the curing is carried out at 80-180℃ for 0.5-20 minutes. Step S4 is followed by a post-treatment step, which is carried out at 120-200°C for 0.5-4.0 h to reduce the residual volatile matter in the cured silicone rubber product to 0.10-1.50 wt%.

[0018] Furthermore, after three consecutive batches of preparation, the hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsiloxane composite reinforced lubricating masterbatch provided in step S1 has an inter-batch coefficient of variation of immobilization rate of no more than 10% and an inter-batch coefficient of variation of residual volatile matter of no more than 15%. After solvent extraction, the cured silicone rubber product obtained in step S4 is subjected to the determination of the coefficient of dynamic friction before extraction and the coefficient of dynamic friction after extraction in accordance with the American Society for Testing and Materials standard D1894. The coefficient of dynamic friction after extraction is divided by the coefficient of dynamic friction before extraction and multiplied by 100% as the coefficient of dynamic friction retention rate, which is 70-100%.

[0019] As a concept of this invention, this invention employs a design that matches a hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch with a two-component addition-curing liquid silicone system. This design primarily aims to achieve a synergistic balance between mechanical strength and durable low-friction performance. Existing systems typically add reinforcing phases such as fumed silica to improve strength, but these reinforcing phases increase interfacial confinement and system viscosity, affecting the distribution of the lubricating phase and processing fluidity. To reduce friction, free lubricating phases are often introduced, but these free components may migrate or soften the network. This invention, through the combined regulation of immobilized interfaces, proportional matching, and addition-curing networks, allows for a controlled distribution of reinforcement and lubrication within the same composite masterbatch, thereby mitigating the adverse effects of these two conventional methods.

[0020] Furthermore, the immobilization rate of the hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsiloxane composite reinforced lubricant masterbatch is calculated using the mass of hydroxyl-terminated polydimethylsiloxane fed as the denominator and the mass of the masterbatch after deducting the mass of unimmobilized hydroxyl-terminated polydimethylsiloxane from the total mass of the fed material as the numerator. The immobilization rate is 70-95 wt%, the content of unimmobilized hydroxyl-terminated polydimethylsiloxane is 0.10-1.50 wt% based on the total mass of the masterbatch, and the residual volatile matter is 0.10-1.50 wt% based on the total mass of the masterbatch. The mass of unimmobilized hydroxyl-terminated polydimethylsiloxane is determined by the toluene extraction mass difference method, and the content of unimmobilized hydroxyl-terminated polydimethylsiloxane is calculated as the ratio of the residual mass of the dried toluene extract to the mass of the masterbatch before extraction.

[0021] Furthermore, in preparing the fumed silica-trimethylsilyl silicate predispersant, 100 parts by weight of fumed silica, 20-80 parts by weight of trimethylsilyl silicate, and 30-120 parts by weight of vinyl-terminated polydimethylsiloxane are added to a vacuum kneading device and mixed at 40-90°C for 0.5-3.0 h. Then, the mixture is degassed at 60-100°C and an absolute pressure of 0.002-0.030 MPa for 0.5-2.0 h to obtain the fumed silica-trimethylsilyl silicate predispersant for mixing with hydroxyl-terminated polydimethylsiloxane.

[0022] Furthermore, in preparing the hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricant masterbatch, 5-30 parts by weight of hydroxyl-terminated polydimethylsiloxane are added to the fumed silica-trimethylsilyl silicate predispersion based on 100 parts by weight of fumed silica. The mixture is then mixed at 60-100°C for 0.5-2.0 h under an industrial nitrogen atmosphere, followed by mixing at 110-150°C and absolute pressure. Heat treatment is carried out at 0.002-0.020 MPa for 1-4 hours; when the content of unfixed hydroxyl-terminated polydimethylsiloxane in the obtained masterbatch is 0.10-1.50 wt% and the residual volatile matter is 0.10-1.50 wt%, the heat treatment is stopped, and the masterbatch is cooled to 20-40°C under an industrial nitrogen atmosphere to obtain the hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch.

[0023] Furthermore, during the preparation of the base adhesive, the vinyl-terminated polydimethylsiloxane added in the final adhesive mixing stage is mixed with the hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsiloxane composite reinforced lubricating masterbatch at 25-80°C for 0.5-3.0 h. The mixing equipment is selected from one or more of a vacuum kneading equipment, a planetary stirring equipment, and a three-roll milling equipment. After mixing, the mixture is degassed for 0.5-2.0 h under an absolute pressure of 0.002-0.030 MPa to obtain the base adhesive for dispensing components A and B.

[0024] Furthermore, the D90 of the hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsiloxane composite reinforced lubricating masterbatch agglomerates in the base adhesive is determined by using the base adhesive sample obtained after mixing the base adhesive as the detection object. Microscopic images of the base adhesive sample are acquired, and the particle size corresponding to the cumulative percentage of 90% in the particle size distribution statistically based on the equivalent circle diameter of the agglomerates is defined as D90. The D90 is 5-80 μm, and the base adhesive that meets the D90 range is used for the dispensing of components A and B.

[0025] Further, component A and component B are mixed at a mass ratio of 1:0.8-1:1.2, and the resulting mixture is cured at 80-180°C for 0.5-20 min by one of injection molding, compression molding, or casting to form a silicone rubber product. The silicone rubber product is then post-treated at 120-200°C for 0.5-4.0 h, and the residual volatile matter after post-treatment is 0.10-1.50 wt% based on the total mass of the product.

[0026] Furthermore, the molar ratio of silane-hydrogen bonds to vinyl groups in the liquid silicone composite material is calculated using the number of molar silane-hydrogen bonds provided by the trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer as the numerator and the number of molar vinyl groups provided by the vinyl-terminated polydimethylsiloxane added in the final mixing stage as the denominator. This molar ratio is controlled to be between 0.80:1 and 1.60:1. The vinyl content is a mass fraction based on the mass of vinyl groups, and the hydrogen content is a mass fraction based on the mass of active hydrogen in the silane-hydrogen bonds. The number of molar silane-hydrogen bonds is calculated by dividing the product of the mass of the hydrogen-containing siloxane copolymer and the hydrogen content by the molar mass of active hydrogen. The number of molar vinyl groups is calculated by dividing the product of the mass of the vinyl-terminated polydimethylsiloxane added in the final mixing stage and the vinyl content by the molar mass of vinyl groups.

[0027] Furthermore, the dynamic friction coefficient of the liquid silicone composite material after curing was measured using the cured sheet silicone rubber sample as the test object, referring to the American Society for Testing and Materials standard D1894. The dynamic friction coefficient before extraction and the dynamic friction coefficient after extraction were recorded for the sheet silicone rubber sample prepared under the same curing and post-treatment conditions, and the dynamic friction coefficient retention rate was calculated by dividing the dynamic friction coefficient after extraction by the dynamic friction coefficient before extraction and multiplying by 100%.

[0028] Furthermore, batch stability was evaluated using three consecutive batches of the hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch. The immobilization rate and residual volatile matter were calculated for each batch of masterbatch. The standard deviation of the immobilization rate of each batch was divided by the average immobilization rate of each batch and multiplied by 100% to obtain the inter-batch coefficient of variation of the immobilization rate. The standard deviation of the residual volatile matter of each batch was divided by the average residual volatile matter of each batch and multiplied by 100% to obtain the inter-batch coefficient of variation of the residual volatile matter. The inter-batch coefficient of variation of the immobilization rate was not greater than 10%, and the inter-batch coefficient of variation of the residual volatile matter was not greater than 15%.

[0029] As another aspect of this invention, the present invention employs a pre-prepared composite reinforced lubricant masterbatch, which is then packaged into components A and B. This is primarily used to achieve, fix, or amplify the aforementioned synergistic effects. Conventional direct mixing methods easily lead to interference between fumed silica thickening, lubricant phase migration, and the platinum catalytic curing window. Increasing the mixing intensity alone may improve dispersion but narrow the processing time, while reducing crosslinking restrictions alone may weaken strength and low migration performance. This invention, by first constructing an immobilized masterbatch, then separating the platinum complex solution with a hydrogen-containing copolymer and 1-ethynylcyclohexanol into different components, and mixing and curing them before use, creates a continuous process chain for the interface immobilization state, hydrosilylation reaction, and post-treatment volatile content control, thereby maintaining the stability of the reinforced lubricant structure during molding and use.

[0030] The hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricant masterbatch mainly addresses the issues of reinforced filler dispersion and low-friction durability, while the trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer mainly addresses the issues of cured network formation and mechanical retention. If immobilization is insufficient in the composite reinforced lubricant masterbatch, the hydroxyl-terminated polydimethylsiloxane easily migrates in a free state, making it difficult to maintain low friction and potentially softening the network. If the proportion of hydrosiloxane copolymer is too high or the molar ratio of silane-hydrogen bonds to vinyl groups is unbalanced, increased crosslinking will increase hardness and interfacial constraint, conversely affecting processing fluidity and surface lubrication stability. This invention, through immobilized interface construction, matching the ratio of fumed silica to trimethylsilyl silicate, separate placement of components A and B, and post-curing treatment, enables the reinforcing phase and lubrication unit to mutually correct each other, ultimately achieving a balance between these inherently contradictory properties.

[0031] Beneficial technical effects 1. By fixing hydroxyl-terminated polydimethylsiloxane to the surface and interface formed by fumed silica-trimethylsilyl silicate, the dispersion state of the filler and the position of the lubrication unit are synergistically regulated. Compared with the direct addition of free lubrication phase, this method helps to reduce migration risk and maintain a more stable low friction performance.

[0032] 2. By controlling the proportions of composite reinforced lubricating masterbatch, trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer, platinum complex solution and 1-ethynylcyclohexanol, the system can achieve a balance between the formation of the cured network and the processing window, reducing the risk of strength reduction, fluidity deterioration or surface instability caused by insufficient or excessive crosslinking.

[0033] 3. By first preparing an immobilized composite reinforced lubricating masterbatch and then packaging the base adhesive into components A and B, the platinum catalytic system and the hydrogen-containing crosslinking components are separated during the storage stage. This is beneficial to improving the operational stability of the two-component addition-type liquid silicone system and enhancing the controllability of the mixing, degassing, and curing processes before molding.

[0034] 4. By limiting the agglomerate D90, fixation rate, residual volatile matter, dynamic friction coefficient retention rate, and batch-to-batch variation coefficient, this invention not only focuses on the performance of individual products, but also on the batch stability of masterbatch and friction retention after low migration, which is beneficial to improving the reliability of products in sealing, sliding contact, and elastic assembly scenarios. Attached Figure Description

[0035] Figure 1 The graph shows the effect of the amount of composite reinforced lubricating masterbatch added on the dynamic friction coefficient and tensile strength in Example 1.

[0036] Figure 2 The graph shows the effect of the molar ratio of silane bonds to vinyl groups on the coefficient of kinetic friction and tensile strength in Example 1.

[0037] Figure 3 The graph shows the effect of the masterbatch fixation rate on the retention rate of the dynamic friction coefficient and the tensile strength in Example 1.

[0038] Figure 4 The graph shows the effect of aggregate D90 on the coefficient of kinetic friction and tear strength in Example 1.

[0039] Figure 5 This is a statistical comparison chart of the fixation rates of Example 1, Comparative Example 6, and Comparative Example 8.

[0040] Figure 6 This is a statistical comparison chart of the content of unfixed hydroxyl-terminated polydimethylsiloxane in Example 1, Comparative Example 6, and Comparative Example 8.

[0041] Figure 7This is a statistical comparison chart of the residual volatile matter in the masterbatch of Example 1, Comparative Example 6, and Comparative Example 8.

[0042] Figure 8 The above is a frequency distribution diagram of the equivalent circle diameter of the aggregates in Example 1 and Comparative Example 7.

[0043] Figure 9 The cumulative distribution of the equivalent circle diameter of the aggregates in Example 1 and Comparative Example 7 is shown in the diagram.

[0044] Figure 10 The graph shows the change in the coefficient of kinetic friction before and after extraction in Example 1, Comparative Example 1, and Comparative Example 8.

[0045] Figure 11 This is a statistical comparison chart of the retention rates of the coefficient of kinetic friction for Example 1, Comparative Example 1, and Comparative Example 8.

[0046] Figure 12 This is a statistical comparison chart of the tensile strength of Example 1, Comparative Example 3, and Comparative Example 4.

[0047] Figure 13 This is a statistical comparison chart of the tear strength of Example 1, Comparative Example 3, and Comparative Example 4.

[0048] Figure 14 The chart shows a statistical comparison of compression set in Example 1, Comparative Example 3, and Comparative Example 4.

[0049] Figure 15 The rheological viscosity curves of Example 1, Comparative Example 5 and Comparative Example 9 at 25°C are shown.

[0050] Figure 16 This is a statistical comparison chart of viscosity growth time for Example 1, Comparative Example 5, and Comparative Example 9.

[0051] Figure 17 This is a statistical comparison chart of the apparent viscosity of Example 1, Comparative Example 5, and Comparative Example 9 at 25°C.

[0052] Figure 18 The images show a comparison of macroscopic optical photographs of the final product of Example 1 and the final product of Comparative Example 7. In Example 1, image a is a macroscopic optical photograph of the final product, which is a sheet-like liquid silicone composite material with a thickness of 4 mm and a composite reinforcing lubricant masterbatch agglomerate D90 of 5 μm in the base adhesive. Image b is a macroscopic optical photograph of the final product of Comparative Example 7, which is a sheet-like liquid silicone composite material with a thickness of 4 mm and a composite reinforcing lubricant masterbatch agglomerate D90 of 120 μm in the base adhesive.

[0053] Figure 19The images show a comparison of the SEM morphology of the final product of Example 1 and the final product of Comparative Example 7. Specifically, a is a low-magnification SEM image of the final product of Example 1, where the sample is a sheet-like liquid silicone composite material with a thickness of 2 mm, and the composite reinforcing lubricant masterbatch agglomerates in the base adhesive have a D90 of 5 μm; b is a low-magnification SEM image of the final product of Comparative Example 7, where the sample is a sheet-like liquid silicone composite material with a thickness of 2 mm, and the composite reinforcing lubricant masterbatch agglomerates in the base adhesive have a D90 of 120 μm; c is a medium-magnification SEM image of the final product of Example 1; d is a medium-magnification SEM image of the final product of Comparative Example 7; e is a high-magnification SEM image of the final product of Example 1; and f is a high-magnification SEM image of the final product of Comparative Example 7.

[0054] Figure 20 The images show a comparison of the TEM structures of the final product of Example 1 and the final product of Comparative Example 7. Specifically, a is a bright-field TEM image of the final product of Example 1, where the sample is a local ultrathin slice of a sheet-like liquid silicone composite material, the primary particle size of the fumed silica is 12 nm, and the D90 of the composite reinforcing lubricant masterbatch agglomerates in the base adhesive is 5 μm; b is a bright-field TEM image of the final product of Comparative Example 7, where the sample is a local ultrathin slice of a sheet-like liquid silicone composite material, and the D90 of the composite reinforcing lubricant masterbatch agglomerates in the base adhesive is 120 μm; c is an HRTEM image of the final product of Example 1; d is an HRTEM image of the final product of Comparative Example 7; e is an EDS surface scan of the final product of Example 1, used to show the distribution of Si and O elements within the observation area; f is an EDS surface scan of the final product of Comparative Example 7, used to show the local distribution of Si and O elements in the agglomerated region.

[0055] Figure 21 The images show the evolution of macroscopic optical photographs from S1 to the final product in Example 1. Specifically, a is a macroscopic optical photograph of S1, a fumed silica-trimethylsilyl silicate predispersant, prepared from vinyl-terminated polydimethylsiloxane, trimethylsilyl silicate, and fumed silica with an average primary particle size of 12 nm; b is a macroscopic optical photograph of S2, a hydroxyl-terminated polydimethylsiloxane immobilized composite reinforced lubricant masterbatch, with a hydroxyl-terminated polydimethylsiloxane immobilization rate of 70 wt% and a residual volatile content of 1.50 wt%; c is a macroscopic optical photograph of S3, a base adhesive or curable mixture, with 15 parts by mass of immobilized composite reinforced lubricant masterbatch added, and the composite reinforced lubricant masterbatch agglomerates with a D90 of 5 μm in the base adhesive; d is a macroscopic optical photograph of the final product, a 5 mm thick sheet-like liquid silicone composite material obtained by curing at 80°C for 0.5 min and then post-treating at 120°C for 0.5 h. Detailed Implementation

[0056] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.

[0057] Example 1 In this embodiment, a low-viscosity two-component addition-type liquid silicone system was prepared by feeding 100 parts by weight of vinyl-terminated polydimethylsiloxane. The vinyl-terminated polydimethylsiloxane used commercially available industrial-grade materials with a viscosity of 500 mPa·s, a vinyl content of 0.05 wt%, and a moisture content ≤0.05 wt%; the fumed silica used commercially available industrial-grade materials with an average primary particle size of 12 nm and a moisture content ≤0.5 wt%; the trimethylsilyl silicate used commercially available industrial-grade materials with a purity ≥98%; the hydroxyl-terminated polydimethylsiloxane used commercially available industrial-grade materials with a hydroxyl content of 0.80 wt%; the trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer used commercially available industrial-grade materials with a hydrogen content of 0.15 wt%; the zero-valent platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex solution used commercially available industrial-grade materials; and the 1-ethynylcyclohexanol used commercially available industrial-grade materials with a purity ≥98%.

[0058] Step B1: Add 100 parts by weight of fumed silica, 20 parts by weight of trimethylsilyl silicate, and 30 parts by weight of vinyl-terminated polydimethylsiloxane to a vacuum kneading device. The order of addition is as follows: first add vinyl-terminated polydimethylsiloxane, then add trimethylsilyl silicate, and finally add fumed silica in three batches. After each addition, knead at 45 rpm for 10 minutes.

[0059] Step B2: Mix the material obtained in step B1 at 40℃ for 0.5h, and maintain the temperature fluctuation of the equipment jacket not exceeding ±3℃ during the mixing process; then degas at 60℃ and absolute pressure of 0.030MPa for 0.5h. The degassing endpoint is when there are no visible large bubbles on the surface of the material for 5 minutes, thus obtaining fumed silica-trimethylsilyl silicate predispersant.

[0060] Steps A2 and A3: Based on 100 parts by mass of fumed silica, add 5 parts by mass of hydroxyl-terminated polydimethylsiloxane to the fumed silica-trimethylsilyl silicate predispersant, mix at 60°C for 0.5 h under an industrial nitrogen atmosphere, with the industrial nitrogen purity ≥99.9%, the oxygen content in the equipment controlled below 1.0 vol%, and the stirring speed 50 rpm.

[0061] Step A4: The mixture obtained in Step A3 was heat-treated at 110℃ and 0.020MPa absolute pressure for 1 hour. After heat treatment, it was cooled to 20℃ under an industrial nitrogen atmosphere to obtain a hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsiloxane composite reinforced lubricant masterbatch. The hydroxyl-terminated polydimethylsiloxane immobilization rate in the obtained masterbatch was 70wt%, the content of unimmobilized hydroxyl-terminated polydimethylsiloxane was 0.97wt%, and the residual volatile matter in the masterbatch was 1.50wt%.

[0062] Step S2: Based on 100 parts by mass of vinyl-terminated polydimethylsiloxane, 15 parts by mass of hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricant masterbatch were added. The mixture was stirred at 25°C for 0.5 h using a vacuum kneading device at a kneading speed of 40 rpm. After mixing, the mixture was degassed for 0.5 h under an absolute pressure of 0.030 MPa to obtain the base adhesive. Microscopic images showed that the D90 of the composite reinforced lubricant masterbatch agglomerates in the base adhesive was 5 μm.

[0063] Step S3: Divide the base adhesive into component A and component B, with a mass ratio of 1:0.8. Add a zero-valent platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex solution to component A, ensuring the platinum content in the total mass of the feed components is 5 mg / kg. Add 1.0 part by mass of trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer and 0.01 part by mass of 1-ethynylcyclohexanol to component B. The calculated molar ratio of silane-hydrogen bonds to vinyl groups in the liquid silicone composite material is 0.80:1.

[0064] Step S4: Mix components A and B at 25°C for 3 minutes at a mixing speed of 300 rpm. Inject the resulting mixture into a 2 mm thick sheet mold and cure at 80°C for 0.5 minutes. Then, post-treat at 120°C for 0.5 hours to obtain a liquid silicone composite material product. The residual volatile matter content of the post-treated product is 1.50 wt%.

[0065] Quality testing methods and results: The fixation rate of the masterbatch was determined by the toluene extraction mass difference method. 5.0 g of masterbatch sample was weighed, 100 mL of toluene was added, and the mixture was stirred and extracted at 25 °C for 2 h. The extraction was repeated 3 times. The extracts were combined and dried to constant weight at 60 °C and 0.010 MPa absolute pressure. The residual mass of the dried extract was taken as the mass of unfixed hydroxyl-terminated polydimethylsiloxane. The fixation rate was calculated as the ratio of the mass of hydroxyl-terminated polydimethylsiloxane minus the mass of unfixed hydroxyl-terminated polydimethylsiloxane to the mass of hydroxyl-terminated polydimethylsiloxane. The D90 of the base rubber aggregate was determined by microscopic image acquisition and equivalent circle diameter statistical method. The dynamic friction coefficient of sheet silicone rubber samples was determined according to the dynamic friction measurement method specified in ASTM D1894-24. The samples were tested after equilibration at 23 °C and 50% relative humidity for 24 h. The number of tests was n=3. The resulting product has a dynamic friction coefficient of 0.65, a Shore A hardness of 20, a tensile strength of 5.0 MPa, a tear strength of 15 kN / m, a compression set of 25%, and a dynamic friction coefficient retention rate of 70%.

[0066] Features and application scenarios of this embodiment: This embodiment adopts a relatively conservative low-ratio scheme. The amount of composite reinforced lubricating masterbatch, the amount of hydrogen-containing siloxane copolymer, the platinum content and the amount of inhibitor are all in the low range. The process temperature and processing time are relatively mild, which is suitable for low viscosity, short process and rapid molding of elastic friction-reducing products.

[0067] Example 2 Raw materials and proportions: In this embodiment, a liquid silica gel composite material was prepared based on 100 parts by weight of vinyl-terminated polydimethylsiloxane. The vinyl-terminated polydimethylsiloxane was a commercially available industrial-grade material with a viscosity of 100,000 mPa·s, a vinyl content of 1.20 wt%, and a moisture content ≤0.05 wt%; the fumed silica was a commercially available industrial-grade material with an average primary particle size of 12 nm and a moisture content ≤0.5 wt%; the trimethylsilyl silicate was a commercially available industrial-grade material with a purity ≥98%; the hydroxyl-terminated polydimethylsiloxane was a commercially available industrial-grade material with a hydroxyl content of 0.80 wt%; the trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer was a commercially available industrial-grade material with a hydrogen content of 0.89 wt%; the zero-valent platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex solution was a commercially available industrial-grade material; and the 1-ethynylcyclohexanol was a commercially available industrial-grade material with a purity ≥98%.

[0068] Preparation of the pre-dispersion: 100 parts by weight of fumed silica, 80 parts by weight of trimethylsilyl silicate, and 120 parts by weight of vinyl-terminated polydimethylsiloxane were added to a vacuum kneader. The vinyl-terminated polydimethylsiloxane was added first, followed by trimethylsilyl silicate, and then the fumed silica was added in five portions. After each addition, the mixture was kneaded at 60 rpm for 12 minutes. After all the materials were added, the mixture was continued to mix at 90°C for 3.0 hours, and then degassed at 100°C and an absolute pressure of 0.002 MPa for 2.0 hours to obtain the fumed silica-trimethylsilyl silicate pre-dispersion.

[0069] Masterbatch immobilization process: Based on 100 parts by weight of fumed silica, 30 parts by weight of hydroxyl-terminated polydimethylsiloxane were added to the pre-dispersion. The mixture was stirred at 100°C for 2.0 h under an industrial nitrogen atmosphere (purity ≥99.9%) and a stirring speed of 80 rpm. Subsequently, it was heat-treated at 150°C and an absolute pressure of 0.002 MPa for 4 h. After heat treatment, it was cooled to 40°C under an industrial nitrogen atmosphere to obtain a hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch. The immobilization rate of the obtained masterbatch was 95 wt%, the content of unimmobilized hydroxyl-terminated polydimethylsiloxane was 0.45 wt%, and the residual volatile matter content of the masterbatch was 0.10 wt%.

[0070] Preparation of the base adhesive and the two-component system: 100 parts by mass of vinyl-terminated polydimethylsiloxane and 45 parts by mass of hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch were added to a three-roll mill and treated at 80°C for 3.0 h. The roller gaps were successively set to 100 μm, 50 μm, and 25 μm, with each roller gap being cycled 3 times. After treatment, degassing was carried out at an absolute pressure of 0.002 MPa for 2.0 h to obtain the base adhesive. The D90 of the composite reinforced lubricating masterbatch agglomerates in the base adhesive was 80 μm. The base adhesive was divided into component A and component B, with a mass ratio of component A to component B of 1:1.2.

[0071] Curing and post-treatment: Zero-valent platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex solution was added to component A to achieve a platinum content of 40 mg / kg in the total mass of the feed components. 8.0 parts by mass of trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer and 0.20 parts by mass of 1-ethynylcyclohexanol were added to component B. The calculated molar ratio of silane-hydrogen bonds to vinyl groups was 1.60:1. Components A and B were mixed at 25°C for 5 min at a mixing speed of 400 rpm, cured by compression molding at 180°C for 20 min, and then post-treated at 200°C for 4.0 h to obtain a silicone rubber product with a residual volatile content of 0.10 wt%.

[0072] Quality testing methods and results: The fixation rate of the masterbatch was determined by the toluene extraction mass difference method; the residual volatile matter was recorded by the segmented heating weight loss method from 105℃ to 200℃; D90 was determined by the equivalent circle diameter statistical method using microscopic images; the mechanical properties and frictional properties of the product were tested using sheet or dumbbell-shaped samples, which were equilibrated for 24 hours at 23℃ and 50% relative humidity before testing (n=3). The obtained product had a dynamic friction coefficient of 0.20, a Shore A hardness of 80, a tensile strength of 12MPa, a tear strength of 45kN / m, a compression set of 8%, and a dynamic friction coefficient retention rate of 100%.

[0073] The features of this embodiment are: This embodiment adopts an optimized scheme with a higher load, with a higher input of composite reinforced lubricating masterbatch and crosslinking components, and sufficient heat treatment, degassing, curing and post-treatment conditions, making it suitable for sealing sheets, sliding contact gaskets and high-reliability elastic components with high requirements for mechanical retention, low migration and low friction retention.

[0074] Example 3 In this embodiment, a liquid silica gel composite material was prepared using a medium-viscosity vinyl-terminated polydimethylsiloxane. The vinyl-terminated polydimethylsiloxane had a viscosity of 20,000 mPa·s and a vinyl content of 0.60 wt%. The fumed silica was a commercially available industrial-grade material with an average primary particle size of 12 nm. The trimethylsilyl silicate had a purity of ≥98%, the hydroxyl content of the hydroxyl-terminated polydimethylsiloxane was 0.80 wt%, the hydrogen content of the trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer was 0.59 wt%, and the purity of 1-ethynylcyclohexanol was ≥98%.

[0075] To prepare the predispersant, 100 parts by mass of fumed silica, 50 parts by mass of trimethylsilyl silicate, and 75 parts by mass of vinyl-terminated polydimethylsiloxane were added to a planetary mixer. The order of addition was as follows: first, vinyl-terminated polydimethylsiloxane and trimethylsilyl silicate were added, and after stirring for 10 minutes, fumed silica was added in four portions. The mixing temperature was controlled at 65°C, the planetary impeller speed at 120 rpm, and the dispersion disc speed at 800 rpm, and mixing was carried out for 1.8 hours. Subsequently, degassing was performed at 80°C and an absolute pressure of 0.010 MPa for 1.2 hours to obtain the fumed silica-trimethylsilyl silicate predispersant.

[0076] 18 parts by mass of hydroxyl-terminated polydimethylsiloxane were added to the pre-dispersion, based on 100 parts by mass of fumed silica, and mixed at 80°C for 1.2 h under an industrial nitrogen atmosphere. The mixture was then transferred to a jacketed vacuum treatment apparatus and heat-treated at 130°C and 0.010 MPa absolute pressure for 2.5 h. After heat treatment, it was cooled to 30°C under an industrial nitrogen atmosphere to obtain a hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricant masterbatch. The masterbatch had an immobilization rate of 84 wt%, an unimmobilized hydroxyl-terminated polydimethylsiloxane content of 1.19 wt%, and a residual volatile content of 0.70 wt%.

[0077] Based on 100 parts by mass of vinyl-terminated polydimethylsiloxane, 30 parts by mass of hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricant masterbatch were added. The mixture was stirred at 50°C for 1.5 h using a planetary mixer with a planetary impeller speed of 100 rpm and a dispersion disk speed of 600 rpm. After mixing, the mixture was degassed for 1.2 h under an absolute pressure of 0.010 MPa to obtain the base adhesive. Microscopic images showed that the D90 of the composite reinforced lubricant masterbatch agglomerates in the base adhesive was 30 μm.

[0078] The base adhesive was divided into component A and component B, with a mass ratio of 1:1.0. A solution of zero-valent platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex was added to component A to achieve a platinum content of 22 mg / kg in the total mass of the feed components. 4.5 parts by mass of a trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer and 0.10 parts by mass of 1-ethynylcyclohexanol were added to component B. The calculated molar ratio of silane-hydrogen bonds to vinyl groups was 1.20:1.

[0079] Components A and B were mixed at 25°C for 4 minutes at a mixing speed of 350 rpm. The mixture was then poured into a sheet mold using a casting curing method and cured at 130°C for 8 minutes. Following this, a post-treatment at 160°C for 2.0 hours was performed to obtain a liquid silicone composite material product. The residual volatile matter content of the post-treated product was 0.60 wt%.

[0080] Quality testing methods and results: The fixed rate of the masterbatch and the content of unfixed components were calculated using the toluene extraction mass difference method; the D90 of agglomerates was determined by microscopic imaging, identifying no fewer than 300 agglomerates; sheet silicone rubber samples were tested after equilibration at 23℃ and 50% relative humidity for 24 hours. The resulting product had a dynamic friction coefficient of 0.32, a Shore A hardness of 50, a tensile strength of 9.2 MPa, a tear strength of 32 kN / m, a compression set of 14%, and a dynamic friction coefficient retention rate of 88%.

[0081] The applicable scenarios for this embodiment are as follows: This embodiment adopts an intermediate parameter combination and a casting and curing route, taking into account the processing fluidity, masterbatch dispersion and curing network stability, and is suitable for medium hardness friction-reducing seals, flexible gaskets and silicone rubber products that require adaptability to molding methods.

[0082] Example 4 I. Preparation Object and Raw Material State: Liquid silica gel composite material was prepared using vinyl-terminated polydimethylsiloxane as the main component. The vinyl-terminated polydimethylsiloxane was a commercially available industrial-grade material with a viscosity of 5000 mPa·s and a vinyl content of 0.30 wt%. Fumed silica was a commercially available industrial-grade material with an average primary particle size of 12 nm. Trimethylsilyl silicate was a commercially available industrial-grade material with a purity ≥98%. Hydroxyl-terminated polydimethylsiloxane, hydrogen-containing siloxane copolymer, platinum complex solution, and 1-ethynylcyclohexanol were all commercially available industrial-grade materials, wherein the hydrogen content of the hydrogen-containing siloxane copolymer was 0.51 wt%.

[0083] II. Preparation of the predispersant: 100 parts by weight of fumed silica, 65 parts by weight of trimethylsilyl silicate, and 45 parts by weight of vinyl-terminated polydimethylsiloxane were added to a vacuum kneader. First, the vinyl-terminated polydimethylsiloxane was added, followed by the trimethylsilyl silicate. After stirring for 15 minutes, the fumed silica was added in three portions. The materials were mixed at 55°C for 2.4 hours at a kneading speed of 55 rpm, and then degassed at 90°C and an absolute pressure of 0.006 MPa for 1.6 hours to obtain a fumed silica-trimethylsilyl silicate predispersant.

[0084] III. Preparation of Composite Reinforced Lubricating Masterbatch: Based on 100 parts by weight of fumed silica, 12 parts by weight of hydroxyl-terminated polydimethylsiloxane were added to the pre-dispersion. The mixture was stirred at 70°C for 1.6 h under an industrial nitrogen atmosphere at a stirring speed of 65 rpm. Subsequently, it was heat-treated at 140°C and an absolute pressure of 0.006 MPa for 3.2 h. After the heat treatment was stopped, it was cooled to 35°C under an industrial nitrogen atmosphere to obtain a hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch. The obtained masterbatch had a fixation rate of 90 wt%, an unfixed hydroxyl-terminated polydimethylsiloxane content of 0.54 wt%, and a residual volatile content of 0.35 wt%.

[0085] IV. Base Adhesive, Packaging, and Curing: 100 parts by weight of vinyl-terminated polydimethylsiloxane and 22 parts by weight of hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch were first mixed in a vacuum kneading machine at 70°C for 1.0 h, then processed twice by a three-roll mill, and subsequently degassed for 1.6 h under an absolute pressure of 0.006 MPa to obtain the base adhesive. The aggregate D90 of the composite reinforced lubricating masterbatch in the base adhesive was 18 μm. The base adhesive was divided into component A and component B, with a mass ratio of component A to component B of 1:0.9. A platinum complex solution was added to component A to make the platinum content 12 mg / kg; 2.2 parts by weight of hydrogen-containing siloxane copolymer and 0.05 parts by weight of 1-ethynylcyclohexanol were added to component B, with a molar ratio of silane-hydrogen bonds to vinyl groups of 1.00:1. After mixing components A and B, the mixture was cured at 160°C for 12 min and then post-treated at 180°C for 3.0 h to obtain a silicone rubber product with a residual volatile content of 0.20 wt%.

[0086] V. Quality Testing Methods and Results: Three consecutive batches of masterbatch were prepared. Each batch was tested according to the calculation methods for fixation rate and residual volatile matter. The inter-batch coefficient of variation for fixation rate was 6.0%, and the inter-batch coefficient of variation for residual volatile matter was 8.0%. The dynamic friction coefficient of sheet silicone rubber samples was tested after solvent extraction, and the dynamic friction coefficient retention rate was calculated. The obtained product had a dynamic friction coefficient of 0.28, a Shore A hardness of 42, a tensile strength of 8.4 MPa, a tear strength of 28 kN / m, a compression set of 12%, and a dynamic friction coefficient retention rate of 92%.

[0087] VI. Process characteristics and application directions of this embodiment: This embodiment adopts a combination of vacuum kneading and three-roll grinding, with the proportioning parameters in the medium-low load range and sufficient post-processing conditions. It is suitable for elastic seals, flexible contacts and low-friction assemblies that have comprehensive requirements for low migration, batch-to-batch stability and surface friction maintenance.

[0088] Comparative Example 1: Basically the same as Example 1, except that in step S2, the amount of hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch added is 10 parts by mass, vinyl-terminated polydimethylsiloxane is 100 parts by mass, trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer is 1.0 part by mass, platinum content is 5 mg / kg, 1-ethynylcyclohexanol is 0.01 parts by mass, the molar ratio of silane-hydrogen bonds to vinyl groups is 0.80:1, A3 mixing is 60°C and 0.5 h, A4 heat treatment is 110°C, absolute pressure 0.020 MPa and 1 h, base adhesive mixing is 25°C and 0.5 h, base adhesive degassing is 0.030 MPa and 0.5 h, the mass ratio of component A to component B is 1:0.8, curing is 80°C and 0.5 min, and post-treatment is 120°C and 0.5 h.

[0089] Comparative Example 2: Basically the same as Example 1, except that in step S2, the amount of hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch added is 55 parts by mass, vinyl-terminated polydimethylsiloxane is 100 parts by mass, trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer is 1.0 part by mass, platinum content is 5 mg / kg, 1-ethynylcyclohexanol is 0.01 parts by mass, the molar ratio of silane-hydrogen bonds to vinyl groups is 0.80:1, A3 mixing is 60°C and 0.5 h, A4 heat treatment is 110°C, absolute pressure 0.020 MPa and 1 h, base adhesive mixing is 25°C and 0.5 h, base adhesive degassing is 0.030 MPa and 0.5 h, the mass ratio of component A to component B is 1:0.8, curing is 80°C and 0.5 min, and post-treatment is 120°C and 0.5 h.

[0090] Comparative Example 3: Basically the same as Example 1, except that in step S3, the amount of trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer added is 0.5 parts by mass, vinyl-terminated polydimethylsiloxane is 100 parts by mass, composite reinforced lubricating masterbatch is 15 parts by mass, platinum content is 5 mg / kg, 1-ethynylcyclohexanol is 0.01 parts by mass, A3 mixing is 60°C and 0.5 h, A4 heat treatment is 110°C, absolute pressure 0.020 MPa and 1 h, base adhesive mixing is 25°C and 0.5 h, base adhesive degassing is 0.030 MPa and 0.5 h, the mass ratio of component A to component B is 1:0.8, curing is 80°C and 0.5 min, and post-treatment is 120°C and 0.5 h.

[0091] Comparative Example 4: Basically the same as Example 1, except that in step S3, the amount of trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer added is 10.0 parts by weight, vinyl-terminated polydimethylsiloxane is 100 parts by weight, composite reinforced lubricating masterbatch is 15 parts by weight, platinum content is 5 mg / kg, 1-ethynylcyclohexanol is 0.01 parts by weight, A3 mixing is 60°C and 0.5 h, A4 heat treatment is 110°C, absolute pressure 0.020 MPa and 1 h, base adhesive mixing is 25°C and 0.5 h, base adhesive degassing is 0.030 MPa and 0.5 h, the mass ratio of component A to component B is 1:0.8, curing is 80°C and 0.5 min, and post-treatment is 120°C and 0.5 h.

[0092] Comparative Example 5: Basically the same as Example 1, except that in step S3, the amount of zero-valent platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex solution added was adjusted to 2 mg / kg of platinum in the total mass of the feed components, 100 parts by mass of vinyl-terminated polydimethylsiloxane, 15 parts by mass of composite reinforced lubricating masterbatch, 1.0 part by mass of hydrogen-containing siloxane copolymer, 0.01 parts by mass of 1-ethynylcyclohexanol, the molar ratio of silane-hydrogen bonds to vinyl groups was 0.80:1, A3 mixing was carried out at 60°C for 0.5 h, A4 heat treatment was carried out at 110°C, absolute pressure of 0.020 MPa for 1 h, base adhesive mixing was carried out at 25°C for 0.5 h, base adhesive degassing was carried out at absolute pressure of 0.030 MPa for 0.5 h, the mass ratio of component A to component B was 1:0.8, curing was carried out at 80°C for 0.5 min, and post-treatment was carried out at 120°C for 0.5 h.

[0093] Comparative Example 6: Basically the same as Example 1, except that the heat treatment time in step A4 is 0.3h, the amount of vinyl-terminated polydimethylsiloxane is 100 parts by weight, the amount of composite reinforced lubricating masterbatch is 15 parts by weight, the amount of hydrogen-containing siloxane copolymer is 1.0 parts by weight, the amount of platinum is 5mg / kg, the amount of 1-ethynylcyclohexanol is 0.01 parts by weight, the molar ratio of silane-hydrogen bonds to vinyl groups is 0.80:1, the mixing time in A3 is 60℃ and 0.5h, the heat treatment temperature in A4 is 110℃, the absolute pressure of heat treatment in A4 is 0.020MPa, the mixing time of the base adhesive is 25℃ and 0.5h, the degassing time of the base adhesive is 0.030MPa and 0.5h, the mass ratio of component A to component B is 1:0.8, the curing time is 80℃ and 0.5min, and the post-treatment time is 120℃ and 0.5h.

[0094] Comparative Example 7: Essentially the same as Example 1, except that in step S2, after mixing the base adhesive, no three-roller or high-shear supplementary dispersion was performed. This resulted in the hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsiloxane composite reinforced lubricant masterbatch having an aggregate D90 of 120 μm in the base adhesive, 100 parts by weight of vinyl-terminated polydimethylsiloxane, 15 parts by weight of the composite reinforced lubricant masterbatch, 1.0 part by weight of the hydrogen-containing siloxane copolymer, and platinum element. The content is 5 mg / kg, 1-ethynylcyclohexanol is 0.01 parts by mass, the molar ratio of silane-hydrogen bonds to vinyl groups is 0.80:1, A3 is mixed at 60℃ for 0.5 h, A4 is heat-treated at 110℃, absolute pressure of 0.020 MPa for 1 h, the base adhesive is degassed at absolute pressure of 0.030 MPa for 0.5 h, the mass ratio of component A to component B is 1:0.8, curing is at 80℃ for 0.5 min, and post-treatment is at 120℃ for 0.5 h.

[0095] Comparative Example 8: Basically the same as Example 1, except that hydroxyl-terminated polydimethylsiloxane is not added in steps A2 to A4. Instead, a pre-dispersion formed by 100 parts by weight of fumed silica, 20 parts by weight of trimethylsilyl silicate, and 30 parts by weight of vinyl-terminated polydimethylsiloxane is used as the reinforcing filler dispersion. The amount of vinyl-terminated polydimethylsiloxane is 100 parts by weight. The amount of reinforcing filler dispersion added is calculated according to the solid and carrier ratio corresponding to Example 1. The amount of hydrogen-containing siloxane copolymer is 1.0 part by weight. The platinum content is 5 mg / kg. The amount of 1-ethynylcyclohexanol is 0.01 parts by weight. The molar ratio of silane-hydrogen bonds to vinyl groups is 0.80:1. The base adhesive is mixed at 25°C and 0.5 h. The base adhesive is degassed at an absolute pressure of 0.030 MPa and 0.5 h. The mass ratio of component A to component B is 1:0.8. The curing is at 80°C and 0.5 min. The post-treatment is at 120°C and 0.5 h. This comparative example was used to investigate the synergistic relationship between the hydroxyl-terminated polydimethylsiloxane immobilized interface and the fumed silica-trimethylsilyl silicate predispersant.

[0096] Comparative Example 9: Essentially the same as Example 1, except that in step S3, components A and B were combined into a single component, stored for 24 hours, and then cured. Specifically, vinyl-terminated polydimethylsiloxane, composite reinforcing lubricant masterbatch, zero-valent platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex solution, trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer, and 1-ethynylcyclohexanol were premixed. The vinyl-terminated polydimethylsiloxane was 100 parts by weight, and the composite reinforcing lubricant masterbatch was 1... Five parts by weight were used, including 1.0 part by weight of the hydrogen-containing siloxane copolymer, 5 mg / kg of platinum, 0.01 part by weight of 1-ethynylcyclohexanol, and a molar ratio of silane-hydrogen bonds to vinyl groups of 0.80:1. A3 was mixed at 60°C for 0.5 h, A4 was heat-treated at 110°C, 0.020 MPa absolute pressure for 1 h, the base adhesive was mixed at 25°C for 0.5 h, the base adhesive was degassed at 0.030 MPa absolute pressure for 0.5 h, curing was at 80°C for 0.5 min, and post-treatment was at 120°C for 0.5 h. This comparative example was used to investigate the synergistic relationship between the separation of components A and B and the inhibition control.

[0097] Characterization and performance testing: Using cured sheet-like silicone rubber samples as the test object, the dynamic friction coefficient and dynamic friction coefficient retention rate were evaluated to examine low friction and retention ability after extraction. The test was performed according to the dynamic friction test method in ASTM D1894-24, "Standard Test Method for Static and Kinetic Coefficients of Friction of Plastic Film and Sheeting". The sample thickness was 2 mm, and the samples were equilibrated for 24 hours at 23℃ and 50% relative humidity. The dynamic friction coefficient before and after extraction was tested with the same contact pair, load, and sliding speed (n=3). The mean, standard deviation, and retention rate were calculated. The corresponding data fields for this experiment are the average dynamic friction coefficient, the standard deviation of the dynamic friction coefficient, the average dynamic friction coefficient retention rate, and the standard deviation of the retention rate, in dimensionless units and %. Lower dynamic friction coefficients and higher retention rates indicate better performance.

[0098] Using cured dumbbell-shaped and sheet-shaped silicone rubber samples as test objects, the Shore A hardness, tensile strength, tear strength, and compression set were evaluated to examine reinforcement and elastic recovery capabilities. Shore A hardness was tested according to ASTM D2240-15 (2021), tensile strength according to ASTM D412-16 (2021), tear strength according to ASTM D624-00 (2020), and compression set according to ASTM D395-18 (2025). Samples were equilibrated at 23℃ and 50% relative humidity for 24 hours, with n=3, and the mean and standard deviation were recorded. Data fields are hardness, tensile strength, tear strength, and compression set, in Shore A, MPa, kN / m, and %.

[0099] Using hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsiloxane composite reinforced lubricant masterbatch as the test object, this study evaluated the immobilization rate, the content of unimmobilized hydroxyl-terminated polydimethylsiloxane, and the residual volatile matter in the masterbatch to investigate the degree of immobilization and low migration basis. The masterbatch was weighed and extracted with toluene. The sample mass was 5.0 g, and the toluene volume was 100 mL. Extraction was carried out at 25 °C for 2 h with stirring, and repeated three times. The extracts were combined and dried to constant weight at 60 °C and 0.010 MPa absolute pressure. The mass difference before and after extraction was used to calculate the immobilization rate, and the residue after drying was used to calculate the content of unimmobilized components. The residual volatile matter was determined using the fractional heating weight loss method (n=3). Data fields include immobilization rate, unimmobilized component content, and residual volatile matter in the masterbatch, in wt%. Higher immobilization rate and lower levels of unimmobilized components and residual volatile matter indicate more thorough control.

[0100] Using the base resin sample obtained after mixing as the test object, this study evaluated the D90 of hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsiloxane composite reinforced lubricant masterbatch agglomerates to investigate the dispersion state of the masterbatch in the base resin. The base resin was pressed into a thin layer, and at least 10 field-of-view images were acquired under transmission or reflection microscopy. The equivalent circle diameter of at least 300 agglomerates was counted, and the particle size corresponding to a cumulative percentage of 90% was calculated (n=3). The data fields are the average D90 and standard deviation of the agglomerate D90, in μm; lower values ​​indicate finer dispersion.

[0101] Using component A, component B, and the mixed liquid silica composite material as test objects, the processing flowability, mixing viscosity, and workable time were evaluated. The aim was to investigate the effects of filler immobilization, inhibitors, and two-component separation on the processing window. Shear rates were recorded from 0.1 to 100 s⁻¹ using a rotational rheometer at 25 °C. -1 Viscosity curves were obtained within the specified range. Tests were conducted using parallel plates with a diameter of 25 mm and a test gap of 1.0 mm. After loading the sample, it was equilibrated at 25°C for 2 minutes before a steady-state shear rate scan was performed. The time required for the viscosity of components A and B to reach twice the initial value after mixing was also recorded (n=3). Data fields included apparent viscosity at 25°C, viscosity rise time, and shear thinning index, in Pa·s, min, and dimensionless units. Moderate viscosity and a longer viscosity rise time indicate better processing adaptability.

[0102] Three consecutive batches of composite reinforced lubricating masterbatch and corresponding silicone rubber products were used as test objects to evaluate batch-to-batch stability and performance retention after low migration, aiming to examine process repeatability. The fixation rate and residual volatile matter were measured for each batch of masterbatch, and the batch-to-batch coefficient of variation for fixation rate and residual volatile matter were calculated. The dynamic friction coefficient of the corresponding products was tested before and after solvent extraction, and the dynamic friction coefficient retention rate was calculated (n=3). Data fields include batch-to-batch coefficient of variation for fixation rate, batch-to-batch coefficient of variation for residual volatile matter, and dynamic friction coefficient retention rate, in percentage (%). Lower coefficients of variation and higher retention rates indicate better batch stability.

[0103] Figure 1 This is a graph showing the effect of the amount of composite reinforced lubricating masterbatch added on the coefficient of dynamic friction and tensile strength in Example 1. Figure 2 The graph shows the effect of the molar ratio of silane bonds to vinyl groups on the coefficient of kinetic friction and tensile strength in Example 1. These graphs are used to illustrate the synergistic effect of formulation composition and crosslinking matching on low friction performance and mechanical properties. Figure 1Based on the basic formulation of Example 1, only the amount of composite reinforced lubricating masterbatch was changed to 12, 15, 22, 30, 38, 45, and 50 parts by mass. As the amount of masterbatch increased, the dynamic friction coefficient showed a decreasing trend, while the tensile strength first increased and then slightly decreased. This indicates that when the masterbatch is insufficient, the lubrication and reinforcement effects are not sufficient, while when the masterbatch is excessive, it may cause local constraint enhancement or increased burden dispersion in the system. When the amount of masterbatch is in a moderate range, it can maintain a high tensile strength while reducing surface friction. Figure 2 Based on the basic system of Example 1, only the molar ratio of silane bonds to vinyl groups was changed to 0.6, 0.8, 1.0, 1.2, 1.4, 1.6, and 1.8. The results showed that the coefficient of dynamic friction and tensile strength were relatively balanced when the molar ratio was in the range of about 1.0–1.4. This indicates that moderate crosslinking is beneficial to the formation of a stable elastic network, which avoids insufficient mechanical support caused by insufficient crosslinking, as well as material hardening and decreased surface smoothness caused by excessive crosslinking.

[0104] Figure 3 This is a graph showing the effect of the masterbatch fixation rate on the retention rate of the dynamic friction coefficient and tensile strength in Example 1. Figure 4 The diagram shows the effect of aggregate D90 on the coefficient of kinetic friction and tear strength in Example 1. Both diagrams further illustrate that the degree of immobilization and the scale of dispersion are important structural factors for achieving low migration, persistent low friction and mechanical stability. Figure 3 Based on the basic preparation conditions of Example 1, only the masterbatch fixation rate was changed to 60%, 70%, 76%, 84%, 90%, 95%, and 98%. As the fixation rate increased, the retention rate of dynamic friction coefficient significantly improved, and the tensile strength remained at a high level. This indicates that fixing hydroxyl-terminated polydimethylsiloxane to the surface and interface formed by fumed silica-trimethylsilyl silicate can reduce the migration of free lubricating phase, thereby improving the ability to retain low friction performance. Figure 4 Based on the basic composition and processing conditions of Example 1, only the D90 of the agglomerates was changed to 3, 5, 20, 40, 60, 80, and 120 μm. The results showed that the agglomerate size was not good for the overall performance. When the D90 was at a lower micrometer level, a higher tear strength could be obtained while maintaining a lower coefficient of dynamic friction, indicating that a moderately refined dispersion structure can reduce local defects and make the reinforcing and lubricating effects synergistic.

[0105] Figure 5 This is a statistical comparison chart of the fixation rates of Example 1, Comparative Example 6, and Comparative Example 8. Figure 6 This is a statistical comparison chart of the content of unfixed hydroxyl-terminated polydimethylsiloxane in Example 1, Comparative Example 6, and Comparative Example 8. Figure 7 The chart shows a statistical comparison of the residual volatile matter in the masterbatch of Example 1, Comparative Example 6, and Comparative Example 8. The formation of the low-migration structure is verified from three aspects: fixation effect, free components, and volatile residues. Figure 5 The results show that the fixation rate of Example 1 is about 70.0%, which is significantly higher than that of Comparative Example 6. Furthermore, Comparative Example 8 did not contain hydroxyl-terminated polydimethylsiloxane and is not suitable for evaluating the fixation rate. This indicates that the bonding stability between the lubricating component and the composite reinforcing phase can be improved by heat treatment fixation. Figure 6 The results show that the content of unfixed hydroxyl-terminated polydimethylsiloxane in Example 1 is about 0.97 wt%, which is lower than that of Comparative Example 6 (about 1.55 wt). This indicates that there is less migratable free lubricating phase in Example 1, which is beneficial to reduce precipitation, migration and frictional performance degradation during subsequent use. Figure 7 The results show that the residual volatile matter in the masterbatch of Example 1 is about 1.50 wt%, which is lower than that in Comparative Example 6 and Comparative Example 8. This indicates that the preparation conditions can better control low molecular weight residues, providing a basis for material odor control, storage stability and subsequent molding reliability.

[0106] Figure 8 The above diagram shows the frequency distribution of the equivalent circle diameter of the aggregates in Example 1 and Comparative Example 7. Figure 9 The images show the cumulative distribution of the equivalent circle diameter of the agglomerates in Example 1 and Comparative Example 7. These images are used to illustrate the differences in the dispersion state of the masterbatch from a particle size statistics perspective. Figure 8 The results show that the equivalent circle diameter distribution of agglomerates in Example 1 is concentrated in the smaller particle size range, while the distribution in Comparative Example 7 is shifted towards the larger particle size and presents a wider distribution, indicating that the composite reinforced lubricating masterbatch in Example 1 is more uniformly dispersed and has fewer local coarse agglomerates. Figure 9 Further, it is shown that the aggregate D90 of Example 1 is about 5 μm, while the aggregate D90 of Comparative Example 7 is about 120 μm. The difference between the two is significant, indicating that controlling the aggregate size to a lower micrometer level can reduce filler enrichment and local structural discontinuity, providing a structural basis for subsequent mechanical strength, tear performance and surface friction stability.

[0107] Figure 10 The graph shows the change in the coefficient of kinetic friction before and after the extraction in Example 1, Comparative Example 1, and Comparative Example 8. Figure 11 The chart shows a statistical comparison of the retention rates of the dynamic friction coefficients of Example 1, Comparative Example 1, and Comparative Example 8. These charts are used to verify the durability of the low-friction performance. Figure 10 The results show that Example 1 maintains a low coefficient of dynamic friction after the extraction time, and the change is smaller than that of Comparative Example 1 and Comparative Example 8, indicating that the structure related to low friction in Example 1 remains relatively stable after the extraction time. Figure 11 The results show that the dynamic friction coefficient retention rate of Example 1 is about 70.0%, which is higher than that of Comparative Example 1 and Comparative Example 8. This further indicates that the immobilized composite reinforced lubricating masterbatch can maintain relatively stable friction behavior after use or extraction, thereby improving the problem of low friction performance in traditional liquid silicone that depends on the free lubricating phase and is prone to migration and decay.

[0108] Figure 12 This is a statistical comparison chart of the tensile strength of Example 1, Comparative Example 3, and Comparative Example 4. Figure 13 This is a statistical comparison chart of the tear strength of Example 1, Comparative Example 3, and Comparative Example 4. Figure 14 The chart shows a statistical comparison of compression set of Example 1, Comparative Example 3, and Comparative Example 4. These three charts are used to illustrate that Example 1 can maintain good mechanical properties and elastic recovery ability while achieving low friction and low migration. Figure 12 The results show that the tensile strength of Example 1 is approximately 5.0 MPa, which is significantly better than that of Comparative Example 3, which has lower strength, and is at a superior level, indicating that the lubrication modification did not cause significant mechanical weakening. Figure 13 The tear strength of Example 1 is shown to be approximately 15.0 kN·m. -1 The value was significantly higher than that of Comparative Example 3 and close to that of Comparative Example 4, indicating that there is a reasonable interfacial interaction between the composite reinforced lubricating masterbatch and the silicone rubber matrix, which can inhibit crack propagation. Figure 14 The results show that the compression set of Example 1 is approximately 25.0%, lower than that of Comparative Examples 3 and 4, indicating that its crosslinked network and filler dispersion are more conducive to elastic recovery and can reduce residual deformation after long-term compression. Comparative Example 4 uses a higher amount of hydrogen-containing siloxane copolymer; excessive silane components may increase local crosslinking constraint and introduce network inhomogeneity, preventing the compression set from decreasing with increasing hydrogen content. Therefore, Example 1 can maintain tensile strength, tear strength, and resilience stability simultaneously under low friction and low migration conditions.

[0109] Figure 15 The rheological viscosity curves of Example 1, Comparative Example 5, and Comparative Example 9 at 25°C are shown. Figure 16 This is a statistical comparison chart of viscosity growth time for Example 1, Comparative Example 5, and Comparative Example 9. Figure 17 The above chart shows the statistical comparison of the apparent viscosity of Example 1, Comparative Example 5, and Comparative Example 9 at 25°C. These three charts are used to evaluate the processing fluidity and operability window of the system. Figure 15 The test shear rate covered 0.1–100 s. -1 Example 1 has a moderate viscosity and changes relatively smoothly with shear rate, while Comparative Example 9 has a significantly higher viscosity, indicating that Example 1 still maintains good fluidity after the introduction of composite reinforced lubricating masterbatch. Figure 16 The results show that the viscosity growth time of Example 1 is about 42 minutes, which is lower than that of Comparative Example 5 and significantly higher than that of Comparative Example 9, indicating that it has both sufficient construction and molding operation time and can maintain a reasonable curing response speed. Figure 17 The results show that the apparent viscosity of Example 1 at 25°C is about 35 Pa·s, which is close to that of Comparative Example 5 and significantly lower than that of Comparative Example 9. This indicates that Example 1 does not significantly sacrifice the initial processing flowability due to low migration immobilization and filler reinforcement, and can meet the processing requirements such as mixing, degassing, coating or injection molding.

[0110] Figure 18 The image shows a macroscopic optical photograph comparison between the final product of Example 1 and the final product of Comparative Example 7, used to illustrate the influence of the dispersion state of the composite reinforced lubricant masterbatch on the macroscopic uniformity of the sheet-like liquid silicone composite material. Figure 18 a is a macroscopic optical photograph of the final product of Example 1. The sample is a sheet-like liquid silicone composite material product with a thickness of 4 mm. The aggregate D90 of the composite reinforcing lubricant masterbatch in the base glue is 5 μm. The sheet has a uniform overall appearance and good surface continuity, indicating that the immobilized composite reinforcing lubricant masterbatch can maintain good molding integrity under appropriate ratio and dispersion conditions. Figure 18 b is a macroscopic optical photograph of the final product of Comparative Example 7. Both samples are sheet-like liquid silicone composite materials with a thickness of 4 mm. However, the D90 of the composite reinforced lubricant masterbatch agglomerates in the base glue is 120 μm, easily showing localized turbidity, white spots, or filler enrichment traces, indicating that insufficient dispersion reduces macroscopic uniformity. Figure 18 It is known that controlling the aggregate D90 to 5μm is beneficial to obtaining sheet-like silicone products with a more uniform appearance and a more continuous structure.

[0111] Figure 19 The image shows a comparison of the SEM morphology of the final product of Example 1 and the final product of Comparative Example 7, which is used to further illustrate the influence of agglomerate size on the surface and cross-sectional microstructure uniformity of the silicone composite material. Figure 19 a is a low-magnification SEM image of the final product of Example 1, showing the large-scale continuous morphology of the 2mm thick sheet product. The D90 of the composite reinforced lubricating masterbatch agglomerates in the base adhesive is 5μm, and no obvious hundred-micron-level filler enrichment area was observed, indicating that the overall dispersion stability is good. Figure 19 b is a low-magnification SEM image of the final product of Comparative Example 7. Since the D90 of the agglomerates increases to 120 μm, it is easier to form large-sized filler agglomerates or local defects in the sheet, indicating that uncontrolled dispersion will weaken the overall structural uniformity. Figure 19 c is a magnified SEM image of the final product of Example 1, showing that the micron-sized masterbatch dispersion domains are uniformly embedded in the cross-linked silicone rubber matrix, indicating that the 5μm-sized aggregate size is beneficial to maintaining the continuity of the matrix. Figure 19 Image d is a magnified SEM image of the final product of Comparative Example 7, showing the outline of 120 μm-sized agglomerates, filler-rich areas, and possible interface discontinuities, indicating that large agglomerates can disrupt local structural uniformity. Figure 19 e is a high-magnification SEM image of the final product of Example 1, showing that the boundary of the filler agglomerates is relatively continuous with the silicone rubber matrix, and there are few defects such as pores, pull-outs and local cracks, indicating that the immobilized masterbatch has good compatibility with the matrix. Figure 19 f is a high-magnification SEM image of the final product of Comparative Example 7. It shows rough edges from large agglomerates, filler accumulation, interfacial voids, or pull-out marks, indicating that excessively large agglomerate size increases local interfacial defects. Figure 19It can be seen that, by controlling the aggregate D90 to 5μm, Example 1 can significantly improve the micro-dispersion state and interface integrity of the liquid silicone composite material.

[0112] Figure 20 The TEM images show a comparison of the final product of Example 1 and the final product of Comparative Example 7, which are used to illustrate the local dispersion state and interfacial structure differences of the composite reinforced lubricant masterbatch in the silicone rubber matrix at a more refined scale. Figure 20 a is a bright-field TEM image of the final product of Example 1, showing that the SiO2 enrichment area in the local ultrathin slice of the sheet-like silicone product is relatively uniformly dispersed, wherein the primary particle size of fumed silica is 12nm and the D90 of the base glue agglomerate is 5μm, indicating that the composite reinforced lubricating masterbatch in Example 1 can form a finer dispersion structure. Figure 20 b is a bright-field TEM image of the final product of Comparative Example 7, showing that the local enrichment of SiO2 is enhanced or the filler is more concentrated. The corresponding base glue agglomerate D90 is 120 μm, indicating that insufficient dispersion will lead to the enrichment of filler in local areas. Figure 20 c is the HRTEM image of the final product of Example 1, showing the local structural features dominated by amorphous SiO2 and polydimethylsiloxane, indicating that the performance improvement of the system mainly comes from the packing dispersion and interface compatibility optimization. Figure 20 d is the HRTEM image of the final product of Comparative Example 7, which shows that the amorphous packing density is higher in local areas of the large agglomerates, indicating that packing agglomeration can change the local phase distribution uniformity. Figure 20 e is the EDS surface scan of the final product of Example 1, showing that Si and O elements are relatively uniformly distributed, indicating that the filler phase containing Si and O has good spatial dispersion in the observation area. Figure 20 f is the EDS surface scan of the final product of Comparative Example 7, showing local enrichment or uneven distribution of Si and O elements, indicating that 120 μm-sized agglomerates cause local concentration of the filler phase. Figure 20 It can be seen that the structural advantages of Example 1 mainly come from the improvement of dispersion scale and the improvement of interface continuity, rather than changes in amorphous structure.

[0113] Figure 21 This is a macroscopic optical photographic evolution diagram of S1 to the final product in Example 1, used to illustrate the continuous formation process of liquid silicone composite material from pre-dispersion, immobilized masterbatch, base glue to the final sheet product. Figure 21 Image a is a macroscopic optical photograph of S1 fumed silica-trimethylsilyl silicate predispersant. The sample was formed by batch kneading, mixing and degassing of vinyl-terminated polydimethylsiloxane, trimethylsilyl silicate and fumed silica with an average primary particle size of 12 nm, indicating that the fumed silica had completed initial wetting and predispersion. Figure 21b is a macroscopic optical photograph of the S2 hydroxyl-terminated polydimethylsiloxane immobilized composite reinforced lubricant masterbatch. The immobilization rate of hydroxyl-terminated polydimethylsiloxane in the masterbatch is 70 wt%, and the residual volatile matter is 1.50 wt%, indicating that the immobilization treatment is beneficial to the formation of a stable composite reinforced lubricant masterbatch. Figure 21 c is a macroscopic optical photograph of S3 base adhesive or curable mixture. The amount of immobilized composite reinforced lubricating masterbatch added in the system is 15 parts by mass, and the D90 of the base adhesive agglomerates is 5 μm, indicating that the masterbatch has achieved a fine micron-level dispersion after mixing and degassing. Figure 21 Image d is a macroscopic optical photograph of the final product. The sample is a 5mm thick sheet-like liquid silicone composite material product obtained by curing at 80℃ for 0.5min and post-treatment at 120℃ for 0.5h. This indicates that the pre-dispersion, immobilization and base gel dispersion structure can be transformed into a stable sheet-like elastomer after cross-linking and curing.

[0114] In conclusion, Figures 1 to 21 The results, verified by examining multiple aspects including formulation ratio, degree of immobilization, aggregate size, extraction stability, mechanical properties, processing rheological properties, and macro- and micro-structures, demonstrate that this liquid silicone composite material effectively alleviates the challenge of simultaneously achieving both mechanical strength and durable low-friction performance, as well as processing fluidity and low migration performance. By immobilizing hydroxyl-terminated polydimethylsiloxane on the surface and interface formed by fumed silica-trimethylsiloxane, and rationally matching it with vinyl-terminated polydimethylsiloxane and hydrogen-containing siloxane copolymers, the interfacial constraint effect of the reinforcing filler and the migration and softening tendency of the lubricating phase can be balanced, thus obtaining a liquid silicone composite material that combines mechanical strength, durable low friction, processing fluidity, and low migration performance.

[0115] Table 1 Performance of Examples and Comparative Examples

[0116]

[0117] As can be seen from the performance of the examples and comparative examples in Table 1, Examples 1–4 exhibit a relatively balanced trend among the coefficient of kinetic friction, retention rate of the coefficient of kinetic friction, tensile strength, tear strength, and compression set. High load or fully immobilized conditions are beneficial for improving strength and friction retention, while medium to low load conditions are beneficial for reducing processing viscosity. In the conventional comparative examples, the mechanical and friction retention data decreased to varying degrees after deviations were made from the composite reinforced lubricant masterbatch, hydrogen-containing siloxane copolymer, platinum content, heat treatment time, or D90. In the synergistic comparative examples 8 and 9, the immobilization interface or the two-component separation control were disrupted, respectively, resulting in simultaneous impacts on low friction retention and mechanical stability, indicating that the trend aligns with the logic of balancing inherently contradictory performance.

[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A liquid silicone composite material, characterized in that, Based on 100 parts by weight of vinyl-terminated polydimethylsiloxane added in the final compounding stage, the following feed components are included: Vinyl-terminated polydimethylsiloxane, 100 parts by weight; Hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch, 15-45 parts by weight, wherein the hydroxyl-terminated polydimethylsiloxane in the masterbatch has a fixation rate of 70-95 wt% relative to its feed amount; Trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer, 1.0-8.0 parts by weight; The zero-valent platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex solution contains 5-40 mg / kg of platinum element in the total mass of the feed components. 1-Ethynylcyclohexanol, 0.01-0.20 parts by mass, and the molar ratio of silicon-hydrogen bonds to vinyl groups in the liquid silicone composite material is 0.80:1-1.60:

1.

2. The liquid silicone composite material according to claim 1, characterized in that, The hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricant masterbatch includes fumed silica, trimethylsilyl silicate, and hydroxyl-terminated polydimethylsiloxane. The hydroxyl-terminated polydimethylsiloxane exists, at least in part, in an immobilized state that is retained after toluene extraction on the surface and interface formed by the fumed silica and the trimethylsilyl silicate. The liquid silicone composite material is cured to form a silicone rubber product.

3. The liquid silicone composite material according to claim 2, characterized in that, The hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsiloxane composite reinforced lubricant masterbatch is prepared through the following steps: A1. Provides a predispersant of fumed silica-trimethylsilyl silicate; A2. Based on 100 parts by weight of the fumed silica, add 5-30 parts by weight of hydroxyl-terminated polydimethylsiloxane; A3. The fumed silica-trimethylsilyl silicate predispersant is mixed with the hydroxyl-terminated polydimethylsiloxane to obtain a mixture; A4. The mixture is heat-treated to fix the hydroxyl-terminated polydimethylsiloxane on the surface and interface of the fumed silica-trimethylsilyl silicate pre-dispersion, to obtain the hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch.

4. The liquid silicone composite material according to claim 3, characterized in that, In step A3, the mixing is carried out under an industrial nitrogen atmosphere at 60-100°C for 0.5-2.0 hours. In step A4, the heat treatment is carried out at 110-150℃ and an absolute pressure of 0.002-0.020MPa for 1-4 hours; After the heat treatment is stopped, the mixture is cooled to 20-40°C under an industrial nitrogen atmosphere to obtain the hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsiloxane composite reinforced lubricating masterbatch. The fixation rate of the hydroxyl-terminated polydimethylsiloxane in the obtained masterbatch was determined by the toluene extraction mass difference method.

5. The liquid silicone composite material according to claim 3, characterized in that, The fumed silica-trimethylsilyl silicate predispersant was prepared by the following steps: B1. Add 100 parts by weight of fumed silica, 20-80 parts by weight of trimethylsilyl silicate and 30-120 parts by weight of vinyl-terminated polydimethylsiloxane to a mixing device; B2. The fumed silica, the trimethylsilyl silicate, and the vinyl-terminated polydimethylsiloxane are mixed and degassed, wherein the mixing is carried out at 40-90°C for 0.5-3.0 h, and the degassed is carried out at 60-100°C and an absolute pressure of 0.002-0.030 MPa for 0.5-2.0 h, to obtain the fumed silica-trimethylsilyl silicate predispersant.

6. The liquid silicone composite material according to claim 2, characterized in that, In the hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricant masterbatch, the mass ratio of fumed silica to trimethylsilyl silicate is 100:20-100:80, and the mass ratio of hydroxyl-terminated polydimethylsiloxane to fumed silica is 5:100-30:

100. The vinyl-terminated polydimethylsiloxane has a viscosity of 500-100000 mPa·s and a vinyl content of 0.05-1.20 wt%. The hydrogen content of the trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer is 0.10-1.60 wt%.

7. The liquid silicone composite material according to claim 1, characterized in that, The liquid silicone composite material is a two-component addition-type liquid silicone system; The two-component addition-type liquid silicone system includes component A and component B; Component A contains the vinyl-terminated polydimethylsiloxane, the hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch, and the zero-valent platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex solution. Component B contains the vinyl-terminated polydimethylsiloxane, the hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch, the trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer, and the 1-ethynylcyclohexanol.

8. A method for preparing a liquid silicone composite material as described in any one of claims 1-7, characterized in that, Includes the following steps: S1. Provide a pre-prepared hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsilyl silicate composite reinforced lubricating masterbatch; S2. According to the feeding ratio specified in claim 1, the vinyl-terminated polydimethylsiloxane and the hydroxyl-terminated polydimethylsiloxane-immobilized fumed silica-trimethylsiloxane composite reinforced lubricating masterbatch are mixed to obtain the base adhesive; S3. The base adhesive is divided into component A and component B. The zero-valent platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex solution is added to component A. The trimethylsilyl-terminated dimethylsiloxane-methylhydrosiloxane copolymer and 1-ethynylcyclohexanol are added to component B. S4. Mix the components A and B and then cure them to obtain a cured silicone rubber product.

9. The preparation method according to claim 8, characterized in that, In step S2, the mixing is carried out at 25-80°C for 0.5-3.0 hours, and the mixing is performed using one or more of a vacuum kneading device, a planetary mixer, or a three-roll mill. After mixing, the aggregate D90 of the hydroxyl-terminated polydimethylsiloxane immobilized fumed silica-trimethylsiloxane composite reinforced lubricant masterbatch in the base adhesive is 5-80 μm. The base adhesive is degassed for 0.5-2.0 hours under reduced pressure conditions of 0.002-0.030 MPa.

10. The preparation method according to claim 8, characterized in that, In step S3, the mass ratio of component A to component B is 1:0.8 to 1:1.2; In step S4, the curing is one of injection molding curing, compression molding curing, or casting curing, and the curing is carried out at 80-180℃ for 0.5-20 minutes. Step S4 is followed by a post-treatment step, which is carried out at 120-200°C for 0.5-4.0 h to reduce the residual volatile matter in the cured silicone rubber product to 0.10-1.50 wt%.

Citation Information

Patent Citations

  • Self-lubricating silicone rubber and preparation method thereof

    CN107815124A